International Arbitration and International Public Order.Precision of international public order concept. - Zappalá Sastoque, Francesco (2017)
It is imperative to clarify the terminology related to the concept of public policy, properly demarcate the principle and define specific guidelines for its application and its different branches, according to the preponderant regulations in the world, emblematic awards and prevalent legal precepts. There is a current theory that distinguishes between local public policy and international public policy. The first is wider than the latter. While domestic public policy is based on local and distitntive fundamental notions of morality and justice derived from the legal and political culture of a nation, the international public policy is accepted by the international community. The public policy can be substantive law or procedural law. The methodology used is documentary.